Community Privilege and Environmental Justice: An Agent‐Based Analysis. Issue 2 (7th November 2016) - Eckerd, Adam; Kim, Yushim; Campbell, Heather E.
Abstract: Several theories compete to explain observed race‐ and ethnicity‐based environmental injustice in society. This paper focuses on analyzing the extent to which firms' siting decisions based on community privilege can explain this outcome. A unique feature of this analysis is that we include analysis of both unwanted land uses (disamenity firms) and desired land uses (amenity firms). The environmental justice analysis of amenities other than green spaces is rare, but amenities are crucial components of urban areas to which environmental justice studies must attend. We use an agent‐based model to explore community outcomes when environmental disamenities choose locations based on low community privilege, and compare this with scenarios in which disamenities only seek to minimize the cost of land. We also assess differences in environmental justice outcomes when amenities choose locations in areas with high community privilege. While disamenities' focus on locating in areas with low community privilege indeed affects environmental equity, the effect of amenity location is also important, and there are powerful interaction effects. The importance of privilege‐based location is found in these simulations regardless of which social group—majority or minority—is assumed to be the privileged group. This study suggests a limitation of EJ policies and models that focus on the politics of disamenity siting without considering the politics of amenity siting.